Dosimetry in magnetic fields with dedicated MR-compatible ionization chambers - Shukla, Bhargesh K.; Renkamp, Claudia Katharina; Schrenk, Oliver; Bakenecker, Anna C.; Klüter, Sebastian; Kawrakow, Iwan; Runz, Armin; Burigo, Lucas Norberto; Karger, Christian; Greilich, Steffen; Pfaffenberger, Asja (Physica medica, 2020)
MR-integrated radiotherapy requires suitable dosimetry detectors to be used in magnetic fields. This study investigates the feasibility of using dedicated MR-compatible ionization chambers at MR-integrated radiotherapy devices. MR-compatible ionization chambers (Exradin A19MR, A1SLMR, A26MR, A28MR) were precisely modeled and their relative response in a 6MV treatment beam in the presence of a magnetic field was simulated using EGSnrc. Monte Carlo simulations were carried out with the magnetic field in three orientations: the magnetic field aligned perpendicular to the chamber and beam axis (transverse orientation), the magnetic field parallel to the chamber as well as parallel to the beam axis. Monte Carlo simulation results were validated with measurements using an electromagnet with magnetic field strength upto 1.1 T with the chambers in transverse orientation. The measurements and simulation results were in good agreement, except for the A26MR ionization chamber in transverse orientation. The maximum increase in response of the ionization chambers observed was 8.6% for the transverse orientation. No appreciable change in chamber response due to the magnetic field was observed for the magnetic field parallel to the ionization chamber and parallel to the photon beam. Polarity and recombination correction factor were experimentally investigated in the transverse orientation. The polarity effect and recombination effect were not altered by a magnetic field. This study further investigates the response of the ionization chambers as a function of the chambers’ rotation around their longitudinal axis. A variation in response was observed when the chamber was not rotationally symmetric, which was independent of the magnetic field.